IMPLEMENTASI PERATURAN DIREKTUR JENDERAL PAJAK NOMOR PER-24/PJ/2012 TENTANG TATA CARA PEMBUATAN FAKTUR PAJAK (Studi Kasus pada Wajib Pajak Industri Tekstil di Kantor Wilayah DJP Jawa Barat I) - Asep Nugraha; Dani Rahmat (Program Magister Ilmu Administrasi dan Kebijakan Publik, Pascasarjana, Universitas Pasundan, 2020)
This paper aims to illustrate the implementation of Director General of Taxes Regulation Number PER-24/PJ/2012 and analyze what factors hinder or cause the failure of the implementation of policies regarding the data that must be included in the tax invoice document on textile industry taxpayers registered in the Regional Tax Office of West Java-I, and further intends to explain existing phenomena with relevant theories in administrative science so that they can describe the problem. The results of this study indicate that the implementation of the Director General of Taxes Regulation Number PER-24/PJ/2012 meets the criteria as a policy failure that is the implementation of an unsuccessful policy, which occurs due to unfavorable external conditions so that the policy does not succeed in realizing the desired impact or final outcome. Policies that include data that must be included in tax invoice documents for the purpose of increasing tax compliance can be assessed as having a risk of failure because the policy factors have bad luck because of factors such as: 1) the view of conflicts of interest between administrator actors and policy targets; 2) deemed contrary to the interests of the policy objectives; 3) triggering actions that can be categorized as fraud (fraud); and 4) prone to be misused by taxpayers unlawfully.